Impact of external and internal factors on management accounting practices: a study of Pakistan - Sidra Shahzadi; Rizwan Khan; Maryam Toor; Ayaz ul Haq (Emerald Publishing Limited, 2018)
The accounting system plays an important role in the companyâ€™s organizational structure. The purpose of this paper is to demonstrate that the integration of management accounting practices is subject to coordination between external and internal factors and accounting management practices.Therefore, the authors move to the contingency model to determine the most significant external â€œunexpected factorsâ€ that explain the introduction of management practices for the management of the various stages of development. The exploratory study examines a sample of Pakistani companies from various sectors.This study reveals that the main factors of uncertainty that affect the organizational structure, environmental uncertainty, advanced production technology, just-in-time method strategy, integrated management of quality and structure findings reveal that MAP affected all process and changes all system in simple to complex system in Pakistaniâ€™s industries.This study is to acquisition the impact of external factors on management accounting practices, to find the impact of internal factors on management accounting practices, to establish the management accounting practices undertaken by the companies in Pakistan.The study contributes to the literature by enhancing our understanding for the impact of external and internal factors on management accounting practices in Pakistan.